Experiences of sport coordinators in a physical education professional development programme - Zeller, D.; Roux, C. J. (My University, 2020)
Physical education (PE) is an essential component of the school curriculum. However, studies show that many facilitators responsible for the delivery of PE in South African schools possibly lack the requisite specialist skills for effective PE delivery. Such facilitators can therefore be assisted with in-service training and professional development (PD) interventions to equip them with the relevant PE teaching skills. The purpose of this study was to analyse sport coordinators’ views about the attributes of effective development of non-specialist PE teachers or programme facilitators in South African schools. A qualitative interpretive paradigm was used to conduct a case study among 32 sport coordinators who taught Foundation Phase PE in 32 schools in the North-West Province of South Africa. The training model of PD was used to design the intervention, which included four different workshops held over one year. Data were obtained by using three semi-structured questionnaires, which were completed at different stages during the intervention and consequently analysed using the conventional content analysis approach. The most significant finding was that continuous training and support should not be considered as optional, but rather a necessity. Both the selection of content and pedagogy used to present the programme need careful consideration. Developing pedagogical content knowledge (PCK) experientially is critical. Modelling of practice and engaging the participants in carefully designed practical activities to demonstrate theoretical principles is preferable compared to the traditional lecture method. Thus, teachers should be assisted, not only to grasp concepts associated with PE as a learning area, but also to develop the pedagogic insight needed to adapt their teaching strategies to the instructional settings in which they find themselves.